Infeksi Laten Tuberkulosis (ILTB) pada Anak dan Vaksin BCG - Fadhilah Amirah Nasution; Dika Amalia (Publikasi Indonesia, 2022)
Tuberculosis (TB) is still a public health problem worldwide. Tuberculosis is an infectious disease caused by the Mycobacterium tuberculosis germ and is one of the 10 leading causes of death worldwide. The methods section should be able to explain the research methods used, including how the procedures were carried out. Tools, materials, media or research instruments must be well described. There is no gold standard for ILTB diagnosis. Tuberculin Skin Test (TST) and Immunoglobulin Release Assay (IGRA) are the WHO recommended ILTB tests. The purpose of TPT is to prevent the occurrence of TB disease so as to reduce the burden of TB. One of the efforts in preventing tuberculosis disease in children is the Bacille Calmette Guerin (BCG) vaccine. BCG vaccine is very effective in preventing tuberculosis in children, where children who do not get BCG vaccine have a 6.87 times higher risk of developing tuberculosis compared to children who get BCG vaccine. The effectiveness of the BCG vaccine in preventing tuberculosis is 85%.